2021
DOI: 10.1186/s12894-021-00828-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid ileal pouch with concomitant anti-refluxing and refluxing ureteroileal anastomosis

Abstract: Purpose We report our preliminary experience of using a hybrid ileal pouch, assessing oncologic outcomes, complications, voiding, and renal function. Methods The study included 25 patients with bladder cancer treated with radical cystectomy with a hybrid ileal pouch with concomitant anti-refluxing and refluxing anastomosis, performed by a single surgeon. The patients were divided into two groups (first and last cases) according to the surgery date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The main characteristics of the included studies are shown in Table 1, the surgical procedures are summarized in Table 2, and the postoperative complications and results are shown in Table 3. There were 5 RCTs [19, 23, 26-28] and 6 cohort studies [20-22, 24, 25, 29] out of the 11 studies. Patients who underwent RC and ONB as UD were included in the studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main characteristics of the included studies are shown in Table 1, the surgical procedures are summarized in Table 2, and the postoperative complications and results are shown in Table 3. There were 5 RCTs [19, 23, 26-28] and 6 cohort studies [20-22, 24, 25, 29] out of the 11 studies. Patients who underwent RC and ONB as UD were included in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who underwent RC and ONB as UD were included in the studies. Only 4 articles [21, 26, 27, 29] addressed the TNM staging of tumor. Five studies [19, 21, 23, 24, 28] reported briefly on suture material in ureteroileal anastomosis technique.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations